2019
DOI: 10.1093/biosci/biz114
|View full text |Cite
|
Sign up to set email alerts
|

Lions, Bylaws, and Conservation Metrics

Abstract: African lions are a significant threat to pastoralists, triggering both retaliatory and nonretaliatory killings that represent a high-profile example of human–wildlife conflict. In the present article, we report on a grassroots campaign to reduce such conflict by shifting agropastoralists’ attitudes toward lion killing and the central role of bylaws in its apparent success. Insofar as all of East Africa's principal protected areas still harboring lions are surrounded by pastoralist populations, the vast majori… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…We wrote this article as a private reflection of our experiences in attempting to coproduce scientific knowledge in Pemba in the light of Beier et al.’s (2016) proposals, so this is our voice and not that of our partners. In other fora, we write extensively with our Tanzanian collaborators (Genda et al., 2022) (Table 1) and comanagers as coauthors (Borgerhoff Mulder et al., 2019). We hope we have shown that employing just some of the ideas advocated by Beier et al.…”
Section: Discussionmentioning
confidence: 99%
“…We wrote this article as a private reflection of our experiences in attempting to coproduce scientific knowledge in Pemba in the light of Beier et al.’s (2016) proposals, so this is our voice and not that of our partners. In other fora, we write extensively with our Tanzanian collaborators (Genda et al., 2022) (Table 1) and comanagers as coauthors (Borgerhoff Mulder et al., 2019). We hope we have shown that employing just some of the ideas advocated by Beier et al.…”
Section: Discussionmentioning
confidence: 99%
“…This may be message-specific. For example, in Mpimbwe, Katavi Region of western Tanzania, we have found that the 7-35 years old age band is most effective for general messaging (Milner-Gulland et al, 2020), but that the views of male household heads on their sons' behavior are particularly critical for controlling illegal lion killing (Borgerhoff Mulder et al, 2019). For any age or gendered group, outside experts need to understand the extent to which new environmental messages challenge and/or support existing knowledge and practice.…”
Section: Looking Down: Sensitive Building Of Local Capacitymentioning
confidence: 99%
“…To make two specific points that might mitigate some of the problems associated with parachute science, we here build on a current collaboration (Figure 1) that has grown out of a long-term research project in western Tanzania (Borgerhoff Mulder et al, 2007). Our joint work includes a campaign against illegal lion killing (Borgerhoff Mulder et al, 2019;Genda et al, 2012), joint guidance of a community-based environmental organization (http://www.lcmo.or.tz/), and various experiences working with local and international conservation organizations and government officials across the country (Caro & Davenport, 2016;Milner-Gulland et al, 2020). First, we emphasize the importance of observing governance structures, maintaining transparency, and responding flexibly to national and regional priorities ("looking up"), and second, we stress the need to keep a close focus on the realities on the ground when designing interventions such as educational programs ("looking down").…”
Section: Introductionmentioning
confidence: 99%
“…For example, to evaluate the success of an intervention designed to reduce illegal lion Panthera leo killing in Tanzania it is more important to monitor shifts in community attitudes toward lion killers and adherence to new communityinstituted bylaws than to census changes in the number of lions in adjacent protected areas. The former indicates cultural and institutional shifts whereas the latter only indirectly gauges illegal offtake given multiple pressures on protected areas and wildlife populations that might confound analysis (Borgerhoff Mulder et al, 2019).…”
Section: Introductionmentioning
confidence: 99%